Drawing conclusions about what co-participants know: Knowledge-probing question–answer sequences in new employee orientation lectures. Issue 5 (October 2019) - Mikkola, Piia; Lehtinen, Esa
This study aims to uncover the processes of interaction through which knowledge acquisition in new employee orientation is monitored and controlled. Using video-recordings of orientation lectures as data, the study focuses on question–answer sequences in which the lecturer's question probes into the state of the employees' knowledge; in particular, it looks at the third turn of the sequence, in which the lecturer comes to a conclusion concerning the participants' knowledge. This is shown to be an unavoidably practical accomplishment, which is contingent on both the often ambivalent responses of the participants and the design of the knowledge-probing question. Also, the lecturer orients to being responsible for providing the employees with the necessary knowledge that they do not have. The study contributes to discussion of the interactional organization of knowledge in institutional settings, and it sheds light on the pros and cons of lectures as interactional encounters.